IMPLEMENTASI KETERAMPILAN MENGELOLA KELAS GURU UNTUK MENGATASI SISWA PASIF PADA MATA PELAJARAN AKIDAH AKLAK DI MTS PAB 4 PATUMBAK - Eka Febrianti; Jamiluddin Marpaung; Hotni Sari Harahap (Journal of Innovative and Creativity, 2026)
This study aims to describe the classroom management skills of Akidah Akhlak teachers, the implementation of these skills in overcoming passive students, and the supporting factors that influence the effectiveness of learning at MTs PAB 4 Patumbak. The background of this research stems from the phenomenon of students who tend to be passive in Akidah Akhlak learning, which requires teachers to apply effective and innovative classroom management strategies. This research employed a qualitative descriptive approach. Data were collected through interviews, observation, and documentation. The informants consisted of the Principal Principal, Akidah Akhlak teacher and students The data were analyzed through the stages of reduction, data presentation, and conclusion drawing. The results of the study reveal that the Akidah Akhlak teacher’s classroom management skills at MTs PAB 4 Patumbak were carried out through well-prepared lesson planning, the use of various methods (short lectures, discussions, role play, and questioning), and the utilization of visual and audiovisual media. The implementation of these skills proved effective in reducing student passivity, as indicated by increased engagement, greater willingness to ask questions, and active participation in discussions and simulations. The main supporting factors included the principal’s supervision, adequate learning facilities, teacher motivation to innovate, and students’ positive responses to the applied methods and media. In conclusion, the classroom management skills of Akidah Akhlak teachers play a crucial role in overcoming passive students and improving the overall quality of learning. Institutional support and sufficient learning facilities are significant factors that strengthen the effectiveness of these skills.